2020
DOI: 10.1111/jse.12582
|View full text |Cite
|
Sign up to set email alerts
|

Neogene and Quaternary climate changes shaped the lineage differentiation and demographic history of Fokienia hodginsii (Cupressaceae s.l.), a Tertiary relict in East Asia

Abstract: Historical climate oscillations and tectonic events have influenced the speciation and evolutionary history of many organisms. In this study, we chose Fokienia hodginsii (Dunn) A. Henry & H. H. Thomas (Cupressaceae s.l.), a Tertiary relict conifer, for the inference of the demographic history since the Neogene. Five chloroplast regions and two single‐copy nuclear genes were amplified and sequenced in 497 individuals from 28 populations. The chloroplast data showed that F. hodginsii presented a high level of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 86 publications
1
10
0
Order By: Relevance
“…In addition, combined with the obvious phylogeographic structure and ENM results, it seems the F. hodginsii survived in four refuges during the last glacial episodes, which is consistent with the multiple refugia patterns of relict species in subtropical China (Yin et al, 2020). The F. hodginsii population has a relatively high genetic diversity, which may be related to its long history in a variety of geographical habitats (Yin et al, 2018, Yin et al, 2020. However, the fossils (F. shengxianensis He, Sun & Liu, F. catenulata (Bell) R.W.…”
Section: Palaeogeographic and Palaeoecological Implicationssupporting
confidence: 72%
See 4 more Smart Citations
“…In addition, combined with the obvious phylogeographic structure and ENM results, it seems the F. hodginsii survived in four refuges during the last glacial episodes, which is consistent with the multiple refugia patterns of relict species in subtropical China (Yin et al, 2020). The F. hodginsii population has a relatively high genetic diversity, which may be related to its long history in a variety of geographical habitats (Yin et al, 2018, Yin et al, 2020. However, the fossils (F. shengxianensis He, Sun & Liu, F. catenulata (Bell) R.W.…”
Section: Palaeogeographic and Palaeoecological Implicationssupporting
confidence: 72%
“…Available palaeobotanical evidence indicates that the oldest known fossil record of Fokienia is from the Oligocene of Longjing, Jilin, China (Figure 1; Guo and Zhang, 2002). Combined with the previous phylogenetic study of Cupressaceae (Mao et al, 2012;Qu et al, 2017) and fossil records, Yin et al (2020) studied the phylogeography of F. hodginsii based on the molecular markers of chloroplast and single-copy nuclear genes. This analysis revealed that F. hodginsii comprised two major phylogeographic lineages located on either side of the Tanaka-Kaiyong Line, which is considered to be a major phytogeographic boundary in southwest China, separating Sino-Japanese and Sino-Himalayan floristic subkingdoms of East Asia (Li and Li, 1997;Yin et al, 2020).…”
Section: Palaeogeographic and Palaeoecological Implicationsmentioning
confidence: 99%
See 3 more Smart Citations